Identifikasi Ektoparasit Pada Kerbau (Bubalus bubalis) di Pasar Hewan (Waipangali) Kabupaten Sumba Barat Daya - Felicia Feti Ndaga Bani; Julianty Almet; Aji Winarso (Jurnal Veteriner Nusantara, 2022)
One of the disorders experienced by buffalo (Bubalus bubalis) is caused by the presence of ectoparasites such as fleas, ticks and mites. Ectoparasites are parasites that live on the surface of their host's body so that they can cause damage, decreased endurance, and slow growth in buffalo. This study aims to identify various types of ectoparasites in buffalo in Southwest Sumba Regency. The collection of ectoparasites samples was carried out on 70 buffaloes in Waipangali Animal Market of Southwest Sumba Regency. The collection was stored in 70% alcohol, then preserved in the form of a glass preparation and observed using a microscope. The data was analyzed descriptively and then displayed in the form of tables and images. The results of the study are based on the identification that has been done that the types of ectoparasites found attacking buffalo are Haematopinus tuberculatus, Boophilus microplus and Rhipicephalus sp.. The presence of ectoparasites attacks in buffalo can cause disturbances and diseases to death and can be an intermediary of various diseases in buffalo.